The coronavirus conundrum – New knowledge on Long COVID – Vaccines - Romero, José Pacheco (2024)
By the end of 2023, it appeared that SARS-CoV-2 was being controlled, although itsJN.1 variant was infecting more easily, with hospitalizations of older adults and theunvaccinated, but few deaths. Now some light is emerging on Long COVID, how thesequelae affect vital organs and why they persist in a significant number of people.Unfortunately, the brain is one of the most affected organs. Hence, the need forvaccines. We consider this update important as we begin 2024, recognizing the workof Eric Topol as a science communicator who provides a variety of information onwhat is happening with SARS-CoV-2 and COVID-19. Regarding what we have learned,apart from preparing ourselves for future pandemics, we consider it important toavoid loneliness, seek emotional support, practice virtuality and telemedicine, becreative, wash our hands, use masks to protect us from airborne pathogens andsupport vaccines.